Food self-sufficiency of the SEE countries: Is the region prepared for a future crisis? - Tatjana Brankov; Bojan Matkovski; Marija Jeremić; Ivan urić (Sustainability, 2021)
Although the concept of self-sufficiency has been accepted both in developed and developing countries, alternated with periods of its rejections, the food crisis from 2007/08 and COVID-19 pandemic returned focus to the availability of countries to be self-sufficient in food production. Considering the concerns over ensuring food security in many countries, the main objective of this paper is to estimate the ability to fulfill the feed demand of the population in the eight countries of South-East Europe (SEE), which is in crisis conditions, such as pandemic especially important. In that context, the food self-sufficiency ratio (SSR) is calculated for total food production, as well as for different food groups. The next step in the methodological framework was to estimate the influence of different factors on the self-sufficiency ratio, as it depends on natural, financial, economic, and political factors. The results show that the SEE region expresses a high level of SSR in food, so it shows that the region is quite ready to respond to the challenges posed by the crisis. However, as the SEE region is a group of very different countries, regional cooperation should be strengthened as food production is considered.
Keywords: 330; food self-sufficiency; South-East Europe; COVID-19